2020
DOI: 10.1007/s10346-020-01457-9
|View full text |Cite
|
Sign up to set email alerts
|

Landslide precipitation thresholds in Rwanda

Abstract: Regional empirical-statistical thresholds indicating the precipitation conditions initiating landslides are of crucial importance for landslide early warning system development. The objectives of this research were to use landslide and precipitation data in an empirical-statistical approach to (1) identify precipitation-related variables with the highest explanatory power for landslide occurrence and (2) define both trigger and trigger-cause based thresholds for landslides in Rwanda, Central-East Africa. Recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 42 publications
2
24
1
Order By: Relevance
“…Rainfall thresholds all over the world are derived from the statistical analysis of rainfall conditions that have resulted in past landslides (e.g. Guzzetti et al, 2007Guzzetti et al, , 2008Cepeda et al, 2010;Sengupta et al, 2010;Berti et al, 2012;Staley et al, 2013;Zêzere et al, 2015;Segoni et al, 2018;Gariano et al, 2019;Valenzuela et al, 2019;Jordanova et al, 2020;Leonarduzzi and Molnar, 2020;Salinas-Jasso et al, 2020;Uwihirwe et al, 2020). Defining rainfall thresholds over large and diverse areas needs statistically significant information on the occurrence of past landslides and a large amount of rainfall data.…”
Section: Introductionmentioning
confidence: 99%
“…Rainfall thresholds all over the world are derived from the statistical analysis of rainfall conditions that have resulted in past landslides (e.g. Guzzetti et al, 2007Guzzetti et al, , 2008Cepeda et al, 2010;Sengupta et al, 2010;Berti et al, 2012;Staley et al, 2013;Zêzere et al, 2015;Segoni et al, 2018;Gariano et al, 2019;Valenzuela et al, 2019;Jordanova et al, 2020;Leonarduzzi and Molnar, 2020;Salinas-Jasso et al, 2020;Uwihirwe et al, 2020). Defining rainfall thresholds over large and diverse areas needs statistically significant information on the occurrence of past landslides and a large amount of rainfall data.…”
Section: Introductionmentioning
confidence: 99%
“…Others used empirical field tests [39,40] or numerical modelling [3,41], and various studies conducted on LEWS have generally used historical rainfall data together with landslide occurrence records to determine the rainfall threshold inducing landslides [34,[42][43][44][45][46][47][48]. The studies conducted in [22,[49][50][51][52][53][54][55][56] have shown that they have used antecedent rainfall as a key parameter that has a great impact on landslides' occurrence. In this research paper, the parameters considered are rainfall intensity together with soil moisture content (SMC) that can help to achieve a better landslide prediction modelling tool that might be used for LEWS.…”
Section: Introductionmentioning
confidence: 99%
“…The use of rainfall thresholds, combined with susceptibility maps, makes it possible to estimate the probability of landslide triggering (Rossi et al, 2018). Rainfall thresholds all over the world are derived from the statistical analysis of rainfall conditions that have resulted in past landslides (e.g., Guzzetti et al, 2007Guzzetti et al, , 2008Cepeda et al 2010;Sengupta et al, 2010;Ruiz-Villanueva et al 2011;Berti et al, 2012;Staley et al, 2013;Zêzere et al, 2015;Rosi et al, 2016;Peruccacci et al, 2017;Segoni et al, 2018;Gariano et al, 2019;Valenzuela et al, 2019;Jordanova et al, 2020;Leonarduzzi and Molnar, 2020;Salinas-Jasso et al, 2020;Uwihirwe et al, 2020). Defining rainfall thresholds over large and diverse areas needs statistically significant information on the occurrence of past landslides and a large amount of rainfall data.…”
Section: Introductionmentioning
confidence: 99%